If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(2x+4)-1=2(3x-9)+2
We move all terms to the left:
3(2x+4)-1-(2(3x-9)+2)=0
We multiply parentheses
6x-(2(3x-9)+2)+12-1=0
We calculate terms in parentheses: -(2(3x-9)+2), so:We add all the numbers together, and all the variables
2(3x-9)+2
We multiply parentheses
6x-18+2
We add all the numbers together, and all the variables
6x-16
Back to the equation:
-(6x-16)
6x-(6x-16)+11=0
We get rid of parentheses
6x-6x+16+11=0
We add all the numbers together, and all the variables
27!=0
There is no solution for this equation
| 2x-89=175-9x | | 16=8+2h | | 5(c-1)^2=40 | | 6=3n*5 | | 5(3x+2)=-3(3x-5) | | 14+8x=6x-12x | | 2+(x+5)^1/2=x | | 5u-104=881 | | 1/2x+16=38 | | 6a+28-10a=32 | | 4x-138=13x+87 | | r-775/21=6 | | 34=-6=5x | | 5(x-2)+6=-29 | | -5=4+3y | | 23(y+39)=989 | | (0.40)200x=900 | | 19b+32=583 | | -r^2=6r-2=7 | | -17=2v-3 | | 24+2x=3x+2(2*4) | | -52+12x=4x+92 | | 34^2=18^2+x^2 | | 28b-9=747 | | 24+2x=3x+2(2x4) | | 46-c=39 | | 7.3x+2.6=12.4x+1.5 | | -3x-83=6x+97 | | 39=j/7+33 | | 8c+8=56 | | 3(2+x)=3x+(2-x) | | 2/5=-4/5c |